First report of cathepsin E in a teleost (Korean rose bitterling, Rhodeus uyekii): Molecular characterisation and tissue distribution. (May 2020) - Kim, Ju-Won; Cho, Ja Young; Kim, Julan; Kim, Dong-Gyun; Nam, Bo-Hye; Kim, Young-Ok; An, Cheul Min; Kim, Bong-Seok; Park, Jung Youn; Kong, Hee Jeong
Abstract: We isolated and characterised a cDNA encoding the aspartic protease cathepsin E (CTSE) in Korean rose bitterling, Rhodeus uyekii . The full-length Rhodeus uyekii CTSE (RuCTSE) cDNA (1396 bp) contains an open reading frame of 1218 bp, encoding 405 amino acids. Alignment of multiple CTSE protein sequences revealed that two of the aspartyl protease active site residues and a disulphide bond were well-conserved among the other CTSE sequences. Phylogenetic analysis revealed that RuCTSE is most closely related to freshwater fish cathepsin E. RuCTSE is widely expressed in the liver, spleen, ovary, testis, brain, eye, intestine, muscle, fin, stomach, and kidney. This first report of teleost CTSE will provide important information related to the identification of other cathepsin E genes in various fish species and will serve as a useful molecular tool to help clarify biological activities in other teleosts. Highlights: The cathepsin E (CTSE) cDNA was identified from a Korean rose bitterling. Two aspartyl protease active sites and disulphide bond were well-conserved within the aligned sequence. The newly identified RuCTSE is a member of the aspartic protease superfamily through phylogenetic analysis. RuCTSE gene was highly expressed in the liver, spleen, and ovary.